A decline in the coverage and utilization of long-lasting insecticidal nets in Southern Ethiopia: A repeated cross-sectional study - Misganu Endriyas; Tarekegn Solomon; Taye Gari; Teka Samuel; Bernt Lindtjørn (PLoS ONE, 2025)
Background Despite ongoing interventions like long-lasting insecticidal nets (LLIN) distribution and indoor residual spraying, malaria is increasing in Ethiopia. LLIN ownership and utilization vary from time to time and place to place; thus, local evidence of LLIN ownership and use is required. Hence, this study aimed to investigate LLIN ownership, access within household, use, and associated factors using repeated indicators measures. Methods A community-based cross-sectional study with repeated measures was conducted in the Sidama region, southern Ethiopia. The first survey was conducted in February and March 2023, and the second was done from October to December 2023. Multi-stage cluster sampling was employed to select representative households. LLIN coverage and use were estimated per the World Health Organization’s recommendations. Descriptive and multilevel logistic regression analyses were performed, and effect sizes were measured using adjusted odds ratios (AOR) with a 95% confidence interval (CI). Results A total of 1647 households with 8054 individuals were included in the study. Most households were headed by males (89%), farmers (63%), and persons who were unable to read and write (55%). The ownership of at least one LLIN per household was 85% in survey one and dropped to 69% in survey two. The sufficiency of one LLIN for every two people was 36% in survey one and decreased to 29% in survey two. Similarly, the proportion of the population with access to LLIN within households decreased from 66.5% to 54.2%. Moreover, LLIN use dropped from 30.5% to 19.9% between the two surveys. The sufficiency of one LLIN to every two household members was consistently associated with geographical residence, sex, and education of household heads. In contrast, the education of household heads, family size, and age of individuals were consistent predictors of LLIN use. Females were likely to use LLIN during first survey, but no difference was noted during second survey. Conclusion LLIN ownership and use were far below the conventional target (80%). LLIN ownership and utilization declined before the expected period. More than half of the population with access to LLIN within households do not use it. Thus, the malaria programs should consider more LLIN distribution and strengthen LLIN use among population with access to LLIN within their households.